FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI KOPI ARABIKA DI KABUPATEN ENREKANG SULAWESI SELATAN - Syahruni Thamrin (Agric, 2014)
This study aims to identify and analyze the factors that affect the production of Arabica coffee in Enrekang. This study used survey method to conduct interviews with 100 randomly sampled Arabica coffee farmers and site visit to their farms. Factors affecting farm production were analyzed using the Cobb Douglass production function and estimated using least squares method . There were ten coffee production factors assessed: land size, number of productive plants, quantities of Urea, ZA, SP36, KCl, pesticides, herbicides, manure, as well as labor force. Variables that significantly affect Arabica coffee production in Enrekang are the amount of urea, ZA, herbicides, manure, and labor.